2017
DOI: 10.1007/s00104-017-0460-x
|View full text |Cite
|
Sign up to set email alerts
|

R1-Resektion beim Magenkarzinom

Abstract: The results reported in the literature in the context of an R1 situation for a resected gastric carcinoma are not uniform. An R1 situation worsens the prognosis for the long-term survival of patients. This is significant especially for low T stages and lymph node metastasis with 0-≤3 lymph node metastases. In higher tumor stages with extensive lymph node metastases, the survival difference between R0 and R1 resections is lower and frequently no longer significant. The frequency of R1 resection is approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A radical gastrectomy is one of the most important predictors of survival in patients with gastric cancer 1. An nonradical resection, i.e., gastrectomy with a tumor-positive resection margin (incomplete tumor removal), is seen in approximately 1.8–8.4% of patients 2. In the Netherlands, the percentage of incomplete tumor removal is used as one of the quality indicators of gastrectomies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A radical gastrectomy is one of the most important predictors of survival in patients with gastric cancer 1. An nonradical resection, i.e., gastrectomy with a tumor-positive resection margin (incomplete tumor removal), is seen in approximately 1.8–8.4% of patients 2. In the Netherlands, the percentage of incomplete tumor removal is used as one of the quality indicators of gastrectomies.…”
mentioning
confidence: 99%
“…However, data on factors associated with incomplete tumor removal, including preoperative risk assessment models, are scarce. So far, retrospective studies have reported on cohorts from single centers, and only few patients were included 2,7. Also, surgical expertise and quality assurance may play an important role.…”
mentioning
confidence: 99%
“…Additionally, over 60% of the cases were poorly differentiated (Table 1). In the literature, the absence of radical resections is reported to range from 1.8% to 9% for gastric adenocarcinoma and more than 10% for the tumors of gastroesophageal junction [22]. A slightly higher R1 rate can be explained in our sample by the late presentation, with advanced disease at the patient's arrival to surgery.…”
Section: Discussionmentioning
confidence: 56%
“…A slightly higher R1 rate can be explained in our sample by the late presentation, with advanced disease at the patient's arrival to surgery. Ridwelski et al also noted that the rate of R1 resections increases with tumor size (>5 cm), tumor stage (T34), N stage, and poor differentiation [22]. Accordingly, Shiraishi et al observed a poor prognosis for patients with extragastric lymph node involvement with less than a 6% survival rate at five years, regardless of the surgical management [14].…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of R1 resection is also highly variable. 25 The British National Oesophago-Gastric Cancer Audit (NOGCA) reported that up to 29% of the gastrectomies performed in individual hospitals had tumor-positive margins, 26 whereas the Swedish Register for Esophageal and Gastric Cancer (NREV), the percentage of incomplete tumor removal/unknown resection status was 17%. 27 Although it is well known that R1 resection has negative prognostic impact, its significance in specific T stage is yet to be uniformly defined.…”
Section: Discussionmentioning
confidence: 99%